Dampak Praktik Manajemen Laba terhadap Manajemen Pajak Perusahaan - Septian Bayu Kristanto (STIE Indonesia Banking School, 2015)
This study wants to determine the effect of earnings management practices on book tax difference. Based on empirical evidence, companies action related to managing their earnings have intention to manage their tax expense. This phenomenon commonly appears in many countries. The sample in this study is a company engaged in the manufacturing sector between 2010-2013 firm years and listed in Indonesia Stock Exchange. The result in this study confirms that Discretionary accruals have a positive and significant effect on book tax difference. These findings suggest that the greater the level of earnings management by the company, the greater the difference in commercial profit to taxable profit